Production of bambangan (Mangifera pajang Kosterm) juice powder using spray dryer - Nurul’ain Natasha Rivoldiantoe; Willie Yen; Mohd Nazri Abdul Rahman; Norliza Julmohammad; Siti Faridah Mohd Amin; Mohd Azrie Awang; Hasmadi Mamat; Ahmad Hazim Abdul Aziz; Sariah Saalah; Suryani Saallah; Titi Mutiara Kiranawati; Jumardi Roslan (UniSE Press, 2024)
Bambangan fruit juice is a popular beverage in Sabah. However, it has certain limitations, including a relatively short shelf life which is around a week to months depending on the heat treatment processes. Producing bambangan fruit juice in powder form offers an alternative solution to preserve the flavor and ensure its availability throughout the year. Spray drying is a common method for producing fruit juice powder, but it often results in a sticky powder when dealing with concentrated fruit juices. To address this issue, maltodextrin is used as a carrier agent during the spray drying process. This study aimed to identify the optimal conditions for producing bambangan juice powder by examining three key spray drying parameters: maltodextrin concentration (0, 5, 10, 15, 20, and 25%), inlet temperature (150, 160, 170, and 180 °C), and flow rate (20, 30, and 40 rpm). The findings revealed that the best parameters were a maltodextrin concentration of 20%, an inlet temperature of 160 °C, and a flow rate of 20 rpm, yielding a powder recovery rate between 57.0% and 58.8%. These results indicate a high powder yield, exceeding 50% across the parameters studied. The bambangan juice powder produced shows significant potential for applications in various industries, including the food and pharmaceutical sectors.